2011
DOI: 10.2337/db10-1220
|View full text |Cite
|
Sign up to set email alerts
|

The RANKL/RANK/OPG Signaling Pathway Mediates Medial Arterial Calcification in Diabetic Charcot Neuroarthropathy

Abstract: OBJECTIVEThe receptor activator of nuclear factor-κB (RANK), RANK ligand (RANKL), and osteoprotegerin (OPG) signaling pathway (RANKL/RANK/OPG signaling) is implicated in the osteolysis associated with diabetic Charcot neuroarthropathy (CN); however, the links with medial arterial calcification (MAC) seen in people with CN are unclear. This study aimed to investigate the role of RANKL/OPG in MAC in patients with CN.RESEARCH DESIGN AND METHODSEnzyme-linked immunosorbent assay and Bio-plex multiarray technology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
2
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 38 publications
(48 reference statements)
7
86
2
9
Order By: Relevance
“…RANKL-induced calcification has also been demonstrated in other human tissue hierarchies, where calcification occurs in the less differentiated endothelial compartment of the tissue. In vascular tissue, RANKL activation of the ERK pathway is required for insulin-induced osteoblastic differentiation and subsequent calcification, and in aortic tissue, RANKL-induced calcification is inhibited by estrogen [42][43][44]. This supports our observation in the PMEC and implies RANKL may be involved in breast epithelial calcifications.…”
Section: Discussionsupporting
confidence: 81%
“…RANKL-induced calcification has also been demonstrated in other human tissue hierarchies, where calcification occurs in the less differentiated endothelial compartment of the tissue. In vascular tissue, RANKL activation of the ERK pathway is required for insulin-induced osteoblastic differentiation and subsequent calcification, and in aortic tissue, RANKL-induced calcification is inhibited by estrogen [42][43][44]. This supports our observation in the PMEC and implies RANKL may be involved in breast epithelial calcifications.…”
Section: Discussionsupporting
confidence: 81%
“…This proinflammatory cytokine activity has also been described as a part of the etiology model [24, 31]. In our study, we found that coronary artery disease (CAD) demonstrated an odds ratio of 18.6 with Charcot foot.…”
Section: Discussionsupporting
confidence: 52%
“…Two studies have shown that OPG's ligand TRAIL induces proliferation of VSMCs (Kavurma et al, 2008;Secchiero et al, 2004). Three recent studies showed that the addition of OPG inhibit calcification of VSMCs in vitro (Di Bartolo et al, 2011;Ndip et al, 2011;Schoppet et al, 2011). Moreover, it has been reported that RANKL (Panizo et al, 2009) and TRAIL (Chasseraud et al, 2011) stimulates calcification of VSMCs.…”
Section: Molecular and Cellular Endocrinologymentioning
confidence: 94%